Sebaceous carcinoma of the scalp: Recurrence after treatment and utility of diagnostic cytology - Swagata Dowerah; Mondita Borgohain (Wolters Kluwer Medknow Publications, 2016)
Sebaceous carcinoma (SC) of the eyelid is an aggressive, rare tumor of epidermal appendages, accounting for <1% of all cutaneous malignancies. We report a histopathologically diagnosed case of SC, who presented with multiple swellings on the scalp and cervical lymphadenopathy after surgery and radiotherapy. Fine needle aspiration revealed clusters and dispersed population of cells with high nucleo-cytoplasmic ratio, round to oval nuclei, prominent nucleoli, with moderate to abundant vacuolated cytoplasm. A diagnosis of sebaceous gland adenocarcinoma was given. Smears from the lymph node showed features of metastatic carcinoma. This case highlights that fine needle aspiration cytology is a simple, cost-effective tool for diagnosis of SC and can help in early diagnosis.